Volunteer Activity and the Demands of Work and Family - Gomez, Rafael; Gunderson, Morley (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2003)
AbstractThe importance of volunteer activity for employees, employers and governmental and non-governmental organizations that are increasingly relying on volunteers is discussed, followed by an econometric analysis relating volunteer activity to a variety of characteristics of work and family as well as to personal and demographic characteristics of the volunteers. The analysis is based on Cycle 9 of the Canadian General Social Survey (GSS) of 1994—an ideal data set since it links volunteer activity to a wide range of characteristics of work and family. The results are interpreted through the lens of a household production function framework, highlighting the importance of time cost and income, but also characteristics of work and family.